304 Minimally invasive versus open radical hysterectomy for stage IB2 cervical carcinoma; an updated survival analysis of the national cancer database. (13th November 2020) - Nasioudis, D; Ko, E; Haggerty, A; Cory, L; Giuntoli, RL; Kim, SH; Morgan, MA; Latif, N
Abstract : Introduction: Evaluate outcomes of minimally invasive radical hysterectomy (MIRH) for patients with FIGO (2019) stage IB2 (tumor size ≥2 and <4 cm) cervical carcinoma. Methods: Patients with pathological stage IB2 squamous, adenocarcinoma, adenosquamous carcinoma of the cervix, no history of another tumor, who underwent primary radical hysterectomy and lymphadenectomy with known mode of surgery, diagnosed between 2010–2015 with at least one month of follow-up were drawn from the National Cancer Database. Impact of MIRH (robotic-assisted or traditional laparoscopic) on overall survival (OS) was assessed with the log-rank test. A Cox model was constructed to control for confounders. Results: A total of 1304 patients were identified; 621(47.6%) had open, 134 (10.3%) laparoscopic and 549 (42.1%) robotic-assisted laparoscopic radical hysterectomy. Overall conversion rate was 3.5%. Open and MIRH groups were comparable in terms of age, presence of co-morbidities and histology. Patients in both groups had a median of 18 lymph nodes removed (p=0.83). Patients who had MIRH had shorter hospital stay (median 1 vs 3 days, p<0.001). Unplanned re-admission rates were comparable between open and MIRH groups (3.6% vs 5.3%, p=0.13). Median follow-up was 39.1 months. Patients who underwent MIRH had worse OS compared to those who had an open approach, p=0.006; 4-year OS rates were 88.8% and 93.2% respectively. After controlling for patient age, race, insurance status, histology and presence of lymph-vascular invasion, MIRH was associated with worse survival (HR: 1.90, 95% CI: 1.24, 2.92). Conclusions: MIRH is associated with worse overall survival for patients with pathological stage IB2 cervical carcinoma.